2019
DOI: 10.1002/rnc.4708
|View full text |Cite
|
Sign up to set email alerts
|

Exponential stabilization for nonlinear coupled dynamical systems via impulsive and sampled‐data control with input constraints

Abstract: Summary In this paper, exponential stabilization for nonlinear coupled dynamical systems by considering sampled‐data controller and impulsive controller with input constraints is investigated. Based on polytopic representation approach, some linear matrix inequalities are established to guarantee local exponential stabilization of nonlinear coupled dynamical systems. Moreover, by using polytopic differential inclusion, for the case of the partial input saturation involving in the impulsive controller, we also … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 39 publications
0
11
0
Order By: Relevance
“…However, it may be noneconomic. In recent years, discontinuous feedback control approaches, such as intermittent control [7][8][9][10][11][12] and impulse control, [13][14][15][16] have attracted increasing attention because these controllers can achieve the same purposes as the continuous controllers do. And importantly, discontinuous feedback controllers are more economic than continuous controllers.…”
Section: Introductionmentioning
confidence: 99%
“…However, it may be noneconomic. In recent years, discontinuous feedback control approaches, such as intermittent control [7][8][9][10][11][12] and impulse control, [13][14][15][16] have attracted increasing attention because these controllers can achieve the same purposes as the continuous controllers do. And importantly, discontinuous feedback controllers are more economic than continuous controllers.…”
Section: Introductionmentioning
confidence: 99%
“…Li et al. reported that the stability condition of a nonlinear sampled‐valued control system with input constraints can be reduced to the LMI condition [27]. Omran et al.…”
Section: Introductionmentioning
confidence: 99%
“…12 In recent years, a few researchers have begun to investigate actuator saturation in impulsive control systems. 13,14 But, almost all of the existing results assume the value of effective impulsive control signal can be input accurately.…”
Section: Introductionmentioning
confidence: 99%
“…Then, the estimation of attraction domain considering the actuator saturation into impulsive control design is still an open question 12 . In recent years, a few researchers have begun to investigate actuator saturation in impulsive control systems 13,14 . But, almost all of the existing results assume the value of effective impulsive control signal can be input accurately.…”
Section: Introductionmentioning
confidence: 99%